Fluoride Concentration in Community Water and Bottled Drinking Water: A Dilemma Today - Dhingra, S; Marya, CM; Jnaneswar, A; Kumar, H (Kathmandu University Medical Journal, 2015)
Background Because of the potential for contamination of municipal water supplies, people appear to be turning to alternative sources for their pure drinking water. Objectives The present study analyzed the fluoride concentration in community water and bottled drinking water sold in Faridabad city. Methods A comparative evaluation of fluoride content in community water supply and bottled drinking water was done using ion-selective electrode method. The community water samples were collected from six different areas (i.e. north zone, south zone, east zone, west zone and central zone) in the city from public health water supply taps while bottled drinking water samples were randomly picked from grocery shops or supermarkets. Results The fluoride concentration in the community water supply in this study ranges from 0.11 to 0.26 mg/L with mean fluoride concentration of 0.17 mg/L. The mean concentration of fluoride in bottled drinking water was 0.06 mg/L. The differences observed between mean of two water samples was statistically significant. Conclusion The results obtained from the present study clearly state that the fluoride concentration was insufficient in community water supply from all the areas and also was deficient in bottled drinking water sold in Faridabad city. So, Alternative sources of fluorides should be supplemented for optimal dental benefits from the use of fluoride. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12485 Kathmandu University Medical Journal Vol.11(2) 2013: 117-120